The wolf in the woods: ontological concerns in Empire of Wild - Lantz, Derek (My University, 2021)
A close reading of the cause and treatment of lycanthropy in Cherie Dimaline's Empire of Wild is used to discuss differences between Indigenous and Western views on justice, community, monstrosity, and human nature. Utilizing Rupert Ross's Returning to the Teaching: Exploring Aboriginal Justice to provide first-hand understanding of Indigenous justice concepts, Empire of Wild uses myth to provide a moral impetus for community-driven justice models. This paper looks at how myth is integrated into the story, how it differs from other lycanthrope myths, and what the ramifications of that difference means for both the plot and message of Empire of Wild.
Keywords: lycanthrope myths; Indigenous justice concepts; literary criticism